The Ethiopian Empire: Its boundaries, antiquities and appellations in the eyes of foreign writers - Bayu, Yeshambel Kindie (Ethiopian Journal of Social Sciences, 2024)
According to the ancient division of continents, the Ethiopian Empire was within the continent of Asia and it was bounded, except on the southern part, by water bodies. This Ethiopian Empire was the oldest and precedes all other empires of the ancient world such as Persian, Macedonian and Roman empires, respectively and remained intact for a long period of time even after the above stated empires had collapsed. Moreover, this ancient empire, as described by both sacred and profane histories, is land of origins and it was here where Adam and Eve were created and religious beliefs, alphabets and human civilization in general began. Thus, ancient Ethiopians were called autochthones. Regrettably, however, the Ethiopian antiquity was either concealed or falsified by later writers in subtle ways. This paper attempted to examine ancient and medieval sources, and finally it avers to restore the actual history of the Ethiopian Empire.